The Mitochondrial Contact Site and Cristae Organization System and F1FO-ATP Synthase Crosstalk is a Fundamental Property of Mitochondrial Cristae - Cadena, Lawrence Rudy (Jihočeská univerzita, 2022)
The acquisition of mitochondria from an endosymbiont closely related to extant alphaproteobacteria occurred prior to the divergence of modern eukaryotes. Since then, diverse eukaryotes have not only developed a number of different mechanisms to adapt to their environment regarding growth and proliferation, but perpetuated certain traits that have persisted for eons. This thesis postulates an ancestral mechanism for cristae development in mitochondria involving interplay between two cristae shaping protein complexes, the Mitochondrial Contact Site and Cristae Organization System and F1FO-ATP Synthase, that has remained conserved throughout eukaryotic diversification for over 2 billion years.
The Mitochondrial Contact Site and Cristae Organization System and F1FO-ATP Synthase Crosstalk is a Fundamental Property of Mitochondrial Cristae
Keywords: Mitochondria; MICOS; ATP Synthase; Trypanosoma brucei; evolution; protein interaction; Mitochondria; MICOS; ATP Synthase; Trypanosoma brucei; evolution; protein interaction